Keefektifan model concept sentence terhadap menulis teks eksplanasi Siswa kelas XI SMA Negeri 2 Lubuk Basung - Fitri Mirna Naira Fitri Yani; Indriani Nisja; Ria Satini (CV Putra Publisher, 2022)
This research is motivated by the problem of students having difficulty in arranging words so that students' writing is not yet skilled. This study aims to describe the effect of the use of Concep Sentence learning models on the ability to write text Explanations of class XI SMA N 2 Lubuk Basung students. This type of research is quantitative research using an experimental model. The sample in this study were students of class XI SMA N 2 Lubuk Basung people consisting of 26 people. The data in this study are scores on the ability to write Explanation texts without using the Concep Sentence Model and scores on the ability to write Explanatory texts using the Concep Sentence learning models for class XI SMA N 2 Lubuk Basung . The results of this study can be concluded as follows. First, the ability to write explanatory texts for XI SMA N 2 Lubuk Basung students without using Concept Sentence learning models obtained an average score of 59.48 at a range of 56-65% with sufficient qualifications (C). Secondly, the ability to write explanatory texts for XI SMA N 2 Lubuk Basung students using Concept Sentence models obtained an average value of 71,79 at a range of 66-75% with qualifications of More than Enough (LdC). Third, based on the results of the t-test the results of the hypothesis test are tcount> t table (3,93> 1.71).